MAKING APPLICATION DISTRIBUTION MAP OF TWO TYPES OF MANUFACTURE (TEXTILE AND SHOES) AND RELATED INDUSTRIES USING MICROSOFT VISUAL BASIC 6.0 - Ahmad Hidayat; Yuliana Yuliana, SKom, MMSI (Jurnal Sistem Informasi, 2004)
At this time, especially Indonesia, the industrial sector should continue to beimproved in line with the rapidly evolving technological developments today in orderto achieve maximum results in an effort to boost the national economy. One way isby conducting effectiveness and efficiency in the presentation of all data andinformation industries.Provision of appropriate information and can be processed in a fast time is needed forinvestors who want to invest in industrial especially yes on the industrial sector ofsmall and medium enterprises (SME).Information on industry data that consists of the location of the provinces, industrytype, the name of the industry, the main products, capacity, contact persons andothers as well as species distribution maps display industry (textiles and shoes) andrelated industries is very useful for investors in making decisions about the industrysuitable to be developed based on the distribution of industries in a region.